Efeito das dimensões dos corpos de prova na resistência à flexão de compósitos restauradores - Santos, Sybilla Cristine do Couto [UNESP]; Abi-Rached, Felipe Oliveira [UNESP]; Almeida-Júnior, Antonio Alves [UNESP]; Cruz, Carlos Alberto dos Santos [UNESP] (My University, 2011)
The aim of this study was to evaluate the influence of specimen size, in comparison with the ISO Standard, on the three point flexural strength of resin composite restorative materials Filtek Supreme and Filtek Z-250. Forty specimens were fabricated for each material with the following length, width and thickness measurements (n = 10): 1) 20 × 2 × 2 mm (ISO 4049); 2) 10 × 2 × 1 mm; 3) 10 × 1 × 1 mm; 4) 8 × 0.8 × 0.8 mm. The composites were inserted in a single increment into two-piece metal device and light-polymerized. The specimens were dry stored at 37 ± 1 °C and protected from light for 7 days. After this period, flexural strength was measured by three-point flexure test using MTS 810 equipment, with a load cell of 10 kN at a speed of 0.5 mm/min. For the evaluated sizes, the results showed significant variability (p = 0.00) with values when compared with the ISO Standard (116.700 MPa), being statistically higher for the test specimens measuring 10 × 1 × 1 mm (142.530 MPa), similar for those of 10  ×  2  ×  1  mm (115.815 MPa) and lower for those of 8 × 0.8 × 0.8 mm (86.650 MPa). There was statistical equality (p = 0.08) for the studied composites (Filtek Supreme, 125.270 MPa; Filtek Z-250, 108.130 MPa). Specimens measuring 10 × 2 × 1 mm provided flexural strength values equivalent to those obtained in the sizes recommended by the ISO 4049 standard, with lower consumption of material, energy and time.

O objetivo deste estudo foi avaliar, em relação à norma ISO, o efeito da redução das dimensões dos corpos de prova na resistência à flexão, em três pontos, dos compósitos restauradores de nanopartículas (Filtek Supreme - 3M ESPE) e micro-híbrido (Filtek Z-250 - 3M ESPE). Foram confeccionados 40 corpos de prova para cada material com as seguintes dimensões de comprimento, largura e espessura (n = 10): 1) 20 × 2 × 2 mm (ISO 4049); 2) 10 × 2 × 1 mm; 3) 10 × 1 × 1 mm; 4) 8 × 0,8 × 0,8 mm. Os compósitos foram inseridos em único incremento em matrizes metálicas bipartidas, correspondentes a cada dimensão avaliada, e fotoativados. Os corpos de prova foram armazenados a 37 ± 1 °C, em ambiente seco e protegido de luz, durante 7 dias. Posteriormente, foi realizado o ensaio de resistência à flexão, em três pontos, usando o equipamento MTS 810, com célula de carga de 10 kN e velocidade de 0,5 mm/min. Os resultados mostraram variabilidade significativa para as dimensões avaliadas (p = 0,00), com valores, em relação à norma ISO (116,700 MPa), estatisticamente superiores para os corpos de prova de 10 × 1 × 1 mm (142,530 MPa), semelhantes para os de 10 × 2 × 1 mm (115,815 MPa) e inferiores para os de 8 × 0,8 × 0,8 mm (86,650 MPa). Houve igualdade estatística (p = 0,08) para os compósitos estudados (Filtek Supreme, 125,270 MPa; Filtek Z-250, 108,130  MPa). Corpos de prova de 10 × 2 × 1 mm proporcionaram, com menor consumo de material, energia e tempo, valores de resistência à flexão equivalentes àqueles obtidos nas dimensões preconizadas pela norma ISO 4049
Effect of specimen size on flexural strength of restorative composites
Keywords: Specimen size; Flexural strength; Restorative composites; Dimensão de corpos de prova; Resistência à flexão; Compósitos restauradores